Disaster Diplomacy as an Alternative Approach for Indonesias Instrument of Foreign Policy in ASEAN - Sudirman, Arfin; Putra, Animbyo Cahya (Jurnal Ilmiah Hubungan Internasional, 2018)
ASEAN is one of the regions with the highest rate of disaster vulnerability. Tsunami 2004 has triggered the momentum for Indonesia and ASEAN to deal with disaster-related issues more seriously. Losses and casualties from the catastrophe led to the decision by Indonesian government to put disaster prevention and risk reduction as a priority. Indonesia continues to encourage and supporting ASEAN in order to improve the regionâs capability to deal with natural disaster. Through AADMER (ASEAN Agreement on Disaster Management and Emergency Response) that was signed in July 2005, ASEAN held an unequivocal and defined base in any efforts of disaster management, especially in the ASEAN region. Through Qualitative Methodology, this paper will discuss about how the disaster diplomacy of Indonesia contributes to the improvement of ASEANâs capability in the disaster management, but also examines BNPB as both the backbone and the focal point of Indonesiaâs disaster management, which then leads up to how disaster can abolish certain diplomatic hurdles, as well as improving regional cooperation, and strengthen the Indonesiaâs position as a key country in regional disaster management.